Heterologous expression and enhanced production of β-1,4-glucanase of Bacillus halodurans C-125 in Escherichia coli - Nadia Zeeshan; Saher Naz; Shumaila Naz; Amber Afroz; Muzna Zahur; Safia Zia (Electronic Journal of Biotechnology, 2018)
Background: Recombinant DNA technology enables us to produce proteins with desired properties and insubstantial amount for industrial applications. Endo-1, 4-β-glucanases (Egl) is one of the major enzyme involved in degradation of cellulose, an important component of plant cell wall. The present study was aimed at enhancing the production of endo-1, 4-β-glucanases (Egl) of Bacillus halodurans in Escherichia coli. Results: A putative Egl gene of Bacillus Halodurans was expressed in E. coli by cloning in pET 22b (+). On induction with isopropyl-b-d-1-thiogalactopyranoside, the enzyme expression reached upto ~20% of the cell protein producing 29.2 mg/liter culture. An increase in cell density to 12 in auto-inducing LB medium (absorbance at 600 nm) enhanced β-glucanase production up to 5.4 fold. The molecular mass of the enzyme was determined to be 39 KDa, which is nearly the same as the calculated value. Protein sequence was analyzed by CDD, Pfam, I TASSER, COACH, PROCHECK Servers and putative amino acids involved in the formation of catalytic, substrate and metal binding domains were identified. Phylogenetic analysis of the β-glucanases of B. halodurans was performed and position of Egl among other members of the genus Bacillus producing endo-glucanases was determined. Temperature and pH optima of the enzyme were found to be 60°C and 8.0, respectively, under the assay conditions. Conclusion: Production of endo-1, 4 β-glucanase enzymes from B. halodurans increased several folds when cloned in pET vector and expressed in E. coli. To our knowledge, this is the first report of high-level expression and characterization of an endo-1, 4 β-glucanases from B. halodurans.How to cite: Zeeshan N, Naz S, Naz S et al. Heterologous expression and enhanced production of β-1,4-glucanase of Bacillus halodurans C-125 in E. coli. Electron J Biotechnol 2018;34. https://doi.org/10.1016/j.ejbt.2018.05.001. Keywords: Bacillus halodurans, Cellulases, Cellulose hydrolysis, Degradation of cellulose, Endo-1, 4-β-glucanases, Expression analysis, Heterologous expression, In silico protein characterization, IPTG, pET expression system, Plant cell wall